Understanding User Needs in Health Crisis Risk Monitoring Information System Development: A Lesson from Tasikmalaya District, Indonesia - Iman, Arief Tarmansyah; Kusnanto, Hari; Pertiwi, Ariani Arista Putri (UI Scholars Hub, 2025)
A health crisis risk monitoring information system needs to be developed, especially during the pre-disaster phase; therefore, understanding the needs of prospective users is crucial. This study aimed to investigate the needs of potential users regarding the development of this system. This study employed a qualitative, exploratory approach to gather user needs from stakeholders through interviews (n = 7) and one focus group discussion (n = 12). The data were audio-recorded, transcribed verbatim, and then thematically analyzed using qualitative content analysis. The need for information was related to disaster preparedness and its preferred format. The system should be targeted, multiplatform, support multiple users, and easy to access. Features should include fully integration, advanced capabilities, online access, and the ability to generate fast and actionable information. It is essential to have this system for all users. A system must facilitate decision-making at various levels. The system should contain related information in a standardized format, easily accessible through various platforms and by multiple users, and serve as a tool for providing information for risk mitigation, monitoring, and reporting purposes.